PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT INTERPAK GLOBAL CANINDO BEKASI - Rosmalinda; Arief Syah Safrianto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The purpose of this research is to discover whether there is an effect of training and career development on employee performance either simultaneously and partially. This study is also to compare and improve the results of previous studies. This study was conducted on 63 respondence at PT. Interpak Global Canindo. Data acquisition was using questionnaire with Likert scale. The sampling technique was using saturated samples. From the result, it was found the fact that training and career development simultaneously and partially have a significant effect on employee performance. furthermore, training and career development partially also had a significant effect on employee performance.